Sainte Anastasie et la « liberté » de Zadar : remarques sur le « privilège de liberté » du pape Innocent III au « chapitre de Sainte-Anastasie » (1198) - Gioanni, Stéphane (ASPICE HUNC OPUS MIRUM: Festschrift on the occasion of Nikola Jakšić’s 70th birthday, 2020)
St. Anastasia’s memory played an increasingly important role between the 9th and 12th centuries in the history of the Church and the city of Zadar. This evolution is particularly obvious in the ”privilege of freedom” granted by Pope Innocent III to the ”Chapter of St. Anastasia” on February 6, 1198. While the Church of Zadar was trying to preserve its independence from the Patriarchate of Grado, Venetian aggressions against Zadar and the neighboring islands had increased since 1181. It was in this context that the new Pope Innocent III granted the cathedral chapter the right to choose its bishop freely. In this paper, I will first study the early romanization of the hagiographic legend of this ”foreign saint”, before analyzing the functions of St. Anastasia’s memory, which expresses the close relationship with the papacy, the autonomy of the cathedral chapter and the freedom of Zadar threatened by Venice.